4CPS-212 Prescription and administration of oral medication through the jejunostomy and the nasogastric tube in an intensive care unit: impact of good practices guidelines on clinical practice. (March 2019) - Cavagna, P; Zulian, C; Chirk, C; Cuquel, AC; Perreux, J; Houillez, E; Sanchez, C; Fernandez, C; Lescot, T; Bizet, S; Antignac, M
Abstract : Background: In the intensive care unit (ICU), patients are frequently unable to take oral tablets and capsules due to invasive ventilation or sedation. Therefore, medications are administered by nasogastric tube or jejunostomy. We conducted a study in 2017 to describe prescription and administration of oral medications through nasogastric tube or jejunostomy. From this study, local prescription and administration guidelines were implemented in the ICU. Purpose: Our study aimed to assess the impact of guidelines on prescription and administration quality. Material and methods: We conducted a descriptive study in 2018 among patients with jejunostomy, or nasogastric tube and oral medications prescription and administration. Medical data, drugs prescription data, administration data (methods of preparation and administration) were collected in medical files and by physicians' and nurses' interviews by a clinical pharmacy student using a standardised method. The quality of drugs prescriptions were assessed regarding the adequacy of medication's site of absorption with the administration route; adequacy of pharmaceutical form with the administration route; and prescription of the specific administration route (jejunostomy, nasogastric tube). The quality of drugs administrations were assessed regarding the respect of local guidelines in the preparation method, solvent used and lack of simultaneously mix in the same syringe. The results were compared with a study performed in 2017 by Chi-square test with RStudio software (version 3.2.4). Results: Overall, 385 prescriptions were studied in February and March 2018. Guidelines were consulted by physicians in 65% of prescriptions. Concerning prescriptions, the drug's site of absorption was respected in 93% (versus 81% in 2017) (p<0.0001) and appropriate pharmaceutical forms were used in 64% (versus 37%) (p<0.0001). Unfortunately, 42% of medications were prescribed without specific administration route (versus 20%) (p<0.0001). The residents prescribed more frequently the route of administration (65%) than senior physicians (41%) (p<0.023). Nurses were interviewed for 211 administrations. Preparation methods were consistent with guidelines in 96% (versus 49%) (p<0.0001), and dilution of medication into tap water (recommended solvent) increased (90% versus 34%) (p<0.0001). Simultaneous mix in the same syringe increased without reaching significance (37% versus 29%) (p=0.17). To conclude, four out of six of prescriptions and administrations quality criteria were improved. Conclusion: The guidelines' implementation in the ICU for patients with oral medications through jejunostomy or nasogastric tube improved the quality of prescriptions and administrations. However, improvements are still possible involving clinical pharmacy students to support guidelines. References and/or acknowledgements: No conflict of interest.